Progesterone activates Janus Kinase 1/2 and activators of transcription 1 (JAK1‐2/STAT1) pathway in human spermatozoa. (2nd July 2012) - Sagare‐Patil, V.; Modi, D.
Summary Ejaculated spermatozoa undergo capacitation and acrosome reaction by responding to extrinsic clues and activate signalling cascades to induce protein tyrosine phosphorylation. In the present study, we investigated the existence, the Janus kinase (JAK) and activator of transcription (STAT) pathway and determined its physiological relevance. JAK1 and STAT1 are localised on the equatorial region and the midpiece of their human spermatozoa, JAK2 is detected on the sperm tail. Capacitation leads to phosphorylation of JAK2 but not JAK1 and STAT1. In the uncapacitated sperm, phosphorylated JAK2 (pJAK2) is localised mainly in the tail region; in response to capacitation, the JAK2 is phosphorylated in the midpiece and the head region along with the tail. Progesterone (5 μm) leads to phosphorylation of JAK1, JAK2 and STAT1 in a time‐dependent manner. In progesterone‐treated spermatozoa, the JAK2 in the tail is hyperphosphorylated, the JAK2 in the head and the midpiece is dephosphorylated. We conclude that in human spermatozoa, the JAK1/2 pathway is activated upon capacitation and is further modulated by progesterone; the biological processes controlled by this pathway in sperm need to be elucidated.